2017
DOI: 10.1044/2017_jslhr-h-16-0086
|View full text |Cite
|
Sign up to set email alerts
|

Vocabulary Facilitates Speech Perception in Children With Hearing Aids

Abstract: Children with HAs show deficits in sensitivity to phonological structure but appear to take advantage of vocabulary skills to support speech perception in the same way as children with NH. Further investigation is needed to understand the causes of the gap that exists between the overall speech perception abilities of children with HAs and children with NH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 57 publications
1
33
2
Order By: Relevance
“…Compared to the CNH, all groups of children with hearing loss were significantly poorer in vocabulary as measured by the WASI-II Vocabulary subtest, and these were large effects for all groups. At first blush, this finding seems contradictory to those of Briscoe et al (2001) and Klein et al (2017) who reported no difference in the vocabulary scores of children with and without hearing loss. However, those investigators used naming and recognition tasks, whereas the WASI-II vocabulary task that we used requires verbal definitions.…”
Section: Mechanisms That Support Av-nwrcontrasting
confidence: 83%
See 1 more Smart Citation
“…Compared to the CNH, all groups of children with hearing loss were significantly poorer in vocabulary as measured by the WASI-II Vocabulary subtest, and these were large effects for all groups. At first blush, this finding seems contradictory to those of Briscoe et al (2001) and Klein et al (2017) who reported no difference in the vocabulary scores of children with and without hearing loss. However, those investigators used naming and recognition tasks, whereas the WASI-II vocabulary task that we used requires verbal definitions.…”
Section: Mechanisms That Support Av-nwrcontrasting
confidence: 83%
“…The group with hearing loss performed significantly worse than the normalhearing group at all syllable levels, despite performing no differently on the tests of vocabulary or grammar. In a comparison to 5-to 12-year-olds with normal hearing, the children with mild-to-severe hearing loss scored significantly lower on a nonword serial recall task, but they did not differ from their normal-hearing peers on receptive vocabulary, expressive vocabulary, or articulation (Klein, Walker, Kirby, & McCreery, 2017). Finally, among 47 children in Grades 1 and 5 with slight/mild hearing loss and 96 matched normal-hearing peers, the hearing loss group performed significantly poorer on overall repetition of nonwords from the CNRep but equivalently in the developmental, behavioral, and academic domains (Wake et al, 2006).…”
Section: Does the Nwr Performance Of Children With Hearing Loss Predimentioning
confidence: 70%
“…The exact underlying mechanism for processing efficiency is not known, though it is believed to involve central processing and could involve various cognitive processes including working memory, attention, and effort. There is evidence that both vocabulary ( Klein, Walker, Kirby, & McCreery, 2017 ; McCreery et al., 2017) and working memory (McCreery et al., 2017) significantly impact speech recognition in noise for children. In the current study, we had obtained the estimates of receptive vocabulary (Peabody Picture Vocabulary Test, 4th edition, PPVT-4; L. M. Dunn & Dunn, 2007 ) and nonverbal intelligence (Leiter International Performance Scale, 3rd edition; Roid, Miller, Pomplun, & Koch, 2013 ) for 16 of the 36 children with CI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that children’s pronounced speech-in-noise difficulties reflect their inexperience with language. However, studies that have tested for associations between masked speech recognition and language abilities reveal mixed findings as some studies do not support this association (e.g., Garlock et al, 2001; McCreery and Stelmachowicz, 2011; Nittrouer et al, 2013; Klein et al, 2017; McCreery et al, 2017). Several studies have reported a correlation between children’s speech-in-noise recognition scores and the size of their vocabulary (e.g., McCreery and Stelmachowicz, 2011; Vance and Martindale, 2012), but this relationship has not been observed in other studies (e.g., Eisenberg et al, 2000; Nittrouer et al, 2013).…”
Section: Factors Responsible For Developmental Effectsmentioning
confidence: 99%